Mechanistic Simulation of Salt‐Affected Soil‐Plant‐Atmosphere Continuum Dynamics in Seasonally Frozen Regions - Yihao Xun; Xu Xu; Barret Kurylyk; Xinhu Li; Danning Mu; Guanhua Huang (Water Resources Research)
Abstract The salt‐affected Soil‐Plant‐Atmosphere Continuum (SPAC) is a dynamic, interactive system that is particularly complex in seasonally frozen regions where salt transport, precipitation‐dissolution, and soil freeze‐thaw processes play crucial, interrelated roles. Understanding these coupled processes and representing them with mathematical models is critical for effective management of SPAC systems. This study presents a new mechanistic approach and an improved model that integrates a chemical equilibrium module within a mechanistic‐based transport computational module (modified SHAW model). The chemical equilibrium module determines salt precipitation‐dissolution using thermodynamic theory and explains the effects of efflorescence and subflorescence on system dynamics. The model enables simultaneous solutions for heat, water, and salt transport with chemical equilibrium throughout non‐freezing and freezing seasons, as well as plant growth dynamics. Assessment of the model using laboratory experiments and field studies showed good performance, with coefficient of determination values exceeding 0.65 for simulated and measured evaporation rate, leaf area index, soil water content, salt content, and temperature. Furthermore, a comparison between simulation results considering and neglecting the impact of salt precipitation‐dissolution highlights potential inaccuracies in soil heat‐water‐salt dynamics and plant water use resulting from the omission of this process in mechanistic models.